2008
DOI: 10.1016/j.eurpsy.2007.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Towards a neuroanatomy of autism: A systematic review and meta-analysis of structural magnetic resonance imaging studies

Abstract: Autism may result from abnormalities in specific brain regions and a global lack of integration due to brain enlargement. Inconsistencies in the literature partly relate to differences in the age and IQ of study populations. Some regions may show abnormal growth trajectories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
360
7
10

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(416 citation statements)
references
References 83 publications
(54 reference statements)
36
360
7
10
Order By: Relevance
“…Imaging studies with targeted measurements of the vermis have found it to be smaller in size in autism (Murakami et al, 1989;Hashimoto et al, 1995;Courchesne et al, 2001;Scott et al, 2009). However, the results are not always clear, and reports of overall cerebellar volume are mixed, tending to find an overall larger volume compared to controls (Murakami et al, 1989;Courchesne et al, 2001;Sparks et al, 2002;Stanfield et al, 2008). Likewise, functional imaging studies have found children with ASD to have both reduced ) and increased (Allen and Courchesne, 2003) cerebellar activation during a simple movement task.…”
Section: Autism and The Cerebellummentioning
confidence: 93%
See 1 more Smart Citation
“…Imaging studies with targeted measurements of the vermis have found it to be smaller in size in autism (Murakami et al, 1989;Hashimoto et al, 1995;Courchesne et al, 2001;Scott et al, 2009). However, the results are not always clear, and reports of overall cerebellar volume are mixed, tending to find an overall larger volume compared to controls (Murakami et al, 1989;Courchesne et al, 2001;Sparks et al, 2002;Stanfield et al, 2008). Likewise, functional imaging studies have found children with ASD to have both reduced ) and increased (Allen and Courchesne, 2003) cerebellar activation during a simple movement task.…”
Section: Autism and The Cerebellummentioning
confidence: 93%
“…For example, in post-mortem studies, reduced Purkinje cell numbers are the most common neuropathological finding (Ritvo et al, 1986;Bailey et al, 1998;Kemper and Bauman, 1998;Whitney et al, 2008). Furthermore, imaging studies have found that individuals with ASD exhibit reduced volumes in the cerebellar vermis (Murakami et al, 1989;Hashimoto et al, 1995;Courchesne et al, 2001;Scott et al, 2009), with some tendency for an overall increase in cerebellar volume (Murakami et al, 1989;Courchesne et al, 2001;Sparks et al, 2002;Stanfield et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the human autism literature, meta-analyses examining neuroanatomical phenotypes have revealed some overlap across studies [73][74][75][76]. However, definitive interpretations remain in progress, as individual findings in vivo investigations of brains of people with autism have been replicated in some publications, but display considerable inconsistencies in many aspects.…”
Section: Discoveries Of Neuroanatomical Abnormalities In Mouse Modelsmentioning
confidence: 99%
“…Structural imaging has also demonstrated abnormalities in inter-hemispheric long-range white matter pathways. Corpus callosum volume has been used as an index of inter-hemispheric connectivity, and a reduced corpus callosum volume is one of the most replicated structural findings in ASD [60][61][62][63][64][65]. A diffusion tensor analysis of the corpus callosum also demonstrated significant microstructural differences between ASD and control groups [63,[66][67][68].…”
Section: Discussionmentioning
confidence: 96%